VARIABILITAS GENETIK DAN HERITABILITAS KARAKTER AGRONOMIS GALUR JAGUNG DENGAN TESTER MR 14 - Nur, Amin; Iriany, Nenny R; Takdir M, A (Jurnal Agroteknos, 2013)
The objective of research was to estimate the genetic variability and heritability of inbred line maize agronomic characters as the initiation step of  assessment for assembling of new cultivars.  In dry season 2006, 90 inbred lines of maize from ICERI were evaluated at Village of ILETRI KP. Muneng, District of Probolinggo, Province of East Java.  The design was simple latice design with two replications.   Results showed that plant growth, days of flowering and silking, plant harvested, ear harvested, ear weight, moisture content, yield, ear range and 100 seeds weight had wide genetic variability, while plant height, ear height, days to hervest and ear diameter had narrow genetic variability. Heritability broad sense, for characters plant growth, days of flowering and silking, plant harvested, ear harvested, ear weight, moisture content, yield, ear range, plant height, ear height, days to harvest and 100  seeds  weight  was    classified  medium;  while  for  characters  of    ear  diameter  was classified low.   Therefore, efforts to increase inbred line of maize yield are still promising through improvement of such characters. Keywords: genetik variability, heritability, inbred line